THE INFLUENCE OF CORPORATE GOVERNANCE, CAPITAL INTENSITY, PROFITABILITY AND FINANCIAL DISTRESS ON TAX AVOIDANCE - Fathurachman Kautsar; Harti Budi Yanti (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This study aims to analyze the influence of corporate governance, capital intent, profitability, and financial distress on tax avoidance. This study uses a sample taken of manufacturing companies listed on the Indonesia Stock Exchange (www.idx.co.id) for 2023 so that a final sample of 200 observation data is obtained. The data were analyzed using SPSS software with multiple regression analysis, descriptive analysis, classical assumption test and hypothesis. The results of the test conducted by the researcher can be concluded that GCG has a significant negative effect on tax avoidance, while capital intensity has a significant positive effect on tax avoidance, then the profitability variable has a significant negative effect on tax avoidance and finally financial distress has no effect on tax avoidance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period.